SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

High-definition tDCS of the motor cortex affects prefrontal and primary motor activity differently in young and older adults - Yasra Arif; Peihan J. Huang; Seth D. Springer; Hannah J. Okelberry; Jason A. John; Nathan M. Petro; Grant M. Garrison; Kennedy A. Kress; Kellen M. McDonald; Giorgia Picci; Tony W. Wilson (GeroScience, 2025)

Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

Oscillatory Dynamics Serving Verbal Working Memory Differ in People with HIV and Are Linked To Disease Duration - Kellen M. McDonald; Seth D. Springer; Mikki Schantell; Ryan Glesinger; Lucy K. Horne; Hannah J. Okelberry; Jason A. John; Anna T. Coutant; Madelyn P. Willett; Hallie J. Johnson; Rachel K. Spooner; Tony W. Wilson (Journal of Neuroimmune Pharmacology, 2025)
Background Medical advances have greatly improved the quality of life and extended the longevity of people with HIV (PWH). However, many PWH still develop neurocognitive deficits even in the presence of effective viral suppression, with impairments in verbal working memory (VWM) being among the most common. While previous neuroimaging studies have demonstrated altered neural responses during VWM, the underlying temporal dynamics and their relation to clinical indices of HIV remain poorly understood. Hypothesis PWH will have altered neural oscillatory dynamics in brain regions supporting VWM compared to controls, above and beyond the effect of age, and these oscillatory differences will scale with clinical indices of HIV. Methods 166 participants (77 virally-suppressed PWH, 89 demographically-matched controls) completed a VWM task during magnetoencephalography, which was separated into encoding and maintenance phases. Whole-brain, mixed-model ANCOVAs were performed to assess the effects of HIV status on neural dynamics controlling for age. Results PWH performed significantly worse on the task compared to controls. During encoding, there was a significant interaction of group-by-time window, such that PWH had significantly weaker alpha/beta oscillations in the left inferior frontal, superior temporal, and anterior cingulate relative to controls. Further, weaker activity in the anterior cingulate scaled with increased disease duration. PWH also displayed weaker alpha/beta oscillations during maintenance in frontal, temporal, parietal, anterior cingulate, and cerebellar cortices. Conclusions PWH exhibited weaker task-related oscillatory activity during VWM, which was associated with disease duration in the anterior cingulate. Overall, these findings suggest that HIV modulates the neural dynamics underlying VWM, with progressive effects in some areas.

DNA demethylase augments RNA-directed DNA methylation by enhancing CLSY gene expression in maize and Arabidopsis - Qiang Xu; Qiuxin Kan; Zhixiang Luo; Qiang Zhang; Liang Dong; Nathan M. Springer; Qing Li (Molecular Plant, 2025)

Spatiotemporal Dynamics of Non‐Ecological Speciation in Rubyspot Damselflies ( Hetaerina spp.) - C. Patterson; A. Brennan; H. Cowling; A. González‐Rodríguez; G. F. Grether; L. Mendoza Cuenca; M. Springer; Y. M. Vega‐Sánchez; J. Drury (Molecular Ecology, 2025)
Non‐ecological speciation is a common mode of speciation, which occurs when allopatric lineages diverge in the absence of pronounced ecological differences. Yet, relative to other speciation mechanisms, non‐ecological speciation remains understudied. Numerous damselfly clades are characterised as non‐adaptive radiations (the result of several rounds of non‐ecological speciation without subsequent divergence), but there are few damselfly lineages for which we have a detailed understanding of the spatiotemporal dynamics of divergence. Recent phylogeographic analyses demonstrate that American rubyspot damselflies ( Hetaerina americana sensu lato) actually comprise at least two cryptic lineages that coexist sympatrically across most of Mexico. To broaden our understanding of the dynamics of diversification to other rubyspot lineages, we investigated the phylogeographic history of smoky rubyspot damselflies ( Hetaerina titia ) using genomic data collected across Central and North America. Unexpectedly, we found evidence of reproductive isolation between the highly genetically differentiated Pacific and Atlantic lineages of H. titia in a narrow secondary contact zone on the Isthmus of Tehuantepec, Mexico. We then fit models of historical demography to both H. americana sensu lato and H. titia to place these comparisons in a temporal context. Our findings indicate that Pacific and Atlantic lineages of H. titia split more recently than the broadly sympatric lineages within H. americana sensu lato, supporting key assumptions of the non‐ecological speciation model and demonstrating that these two pairs of sister lineages are at different stages of the speciation cycle.

Impacts of repeated fatiguing exercise on mitochondria in Thoroughbreds - B.D. Williams; L.T. Wesolowski; A.N. DiSilvestro; M. Barshick; K. Mogge; E. Jolley; K. Kaniyamattam; A. Logan; S. Johnson; S.H. White-Springer (Journal of Equine Veterinary Science, 2025)

Multi-Step Forecasting of Meteorological Time Series Using CNN-LSTM with Decomposition Methods - Eluã Ramos Coutinho; Jonni G. F. Madeira; Dérick G. F. Borges; Marcus V. Springer; Elizabeth M. de Oliveira; Alvaro L. G. A. Coutinho (Water Resources Management, 2025)

Metabolic Energy is Stored in a Homeostatic Trans-Membrane Water Barochemical Gradient - Charles S. Springer; Martin M. Pike; Thomas M. Barbara (The Journal of Membrane Biology, 2025)

Establishment of a human 3D in vitro liver-bone model as a potential system for drug toxicity screening - Guanqiao Chen; Yuxuan Xin; Mohammad Majd Hammour; Bianca Braun; Sabrina Ehnert; Fabian Springer; Massoud Vosough; Maximilian M. Menger; Ashok Kumar; Andreas K. Nüssler; Romina H. Aspera-Werz (Archives of Toxicology, 2025)
Drug toxicity is an important cause of chronic liver damage, which in the long term can lead to impaired bone homeostasis through an imbalance in the liver-bone axis. For instance, non-steroidal anti-inflammatory drugs ( e.g., diclofenac), which are commonly used to control pain during orthopaedic interventions, are known to reduce bone quality and are the most prevalent causes of drug-induced liver damage. Therefore, we used human cell lines to produce a stable, reproducible, and reliable in vitro liver-bone co-culture model, which mimics the impaired bone homeostasis seen after diclofenac intake in vivo. To provide the best cell culture conditions for the two systems, we tested the effects of supplements contained in liver and bone cell culture medium on liver and bone cell lines, respectively. Additionally, different ratios of culture medium combinations on bone cell scaffolds and liver spheroids’ viability and function were also analysed. Then, liver spheroids and bone scaffolds were daily exposed to 3–6 µM diclofenac alone or in co-culture to compare and evaluate its effect on the liver and bone system. Our results demonstrated that a 50:50 liver:bone medium combination maintains the function of liver spheroids and bone scaffolds for up to 21 days. Osteoclast-like cell activity was significantly upregulated after chronic exposure to diclofenac only in bone scaffolds co-cultured with liver spheroids. Consequently, the mineral content and stiffness of bone scaffolds treated with diclofenac in co-culture with liver spheroids were significantly reduced. Interestingly, our results show that the increase in osteoclastic activity in the system is not related to the main product of diclofenac metabolism. However, osteoclast activation correlated with the increase in oxidative stress and inflammation associated with chronic diclofenac exposure. In summary, we established a long-term stable liver-bone system that represents the interaction between the two organs, meanwhile, it is also an outstanding model for studying the toxicity of drugs on bone homeostasis.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Identifying the stand properties that support both high biodiversity and carbon storage in German forests - K. Springer; P. Manning; A.L. Boesing; C. Ammer; A.M. Fiore-Donno; M. Fischer; K. Goldmann; G. Le Provost; J. Overmann; L. Ruess; I. Schöning; S. Seibold; et al. (Forest Ecology and Management, 2024)

Spatially explicit models reveal rodents rapidly colonize soybean fields regardless of pre-planting chemical treatment timing for cover crop removal - Jena L. Nierman; Sean M. Murphy; Wendy Leuenberger; Allison G. Davis; John J. Cox; Matthew T. Springer (Crop Protection, 2024)

Who notices Gymnophiona? Google Trends data reveal interesting trends for recent amphibian species - Branden Holmes; Janine M. Ziermann; Artur Strzelecki; Steffen Springer; Michael Zieger (Ecological Complexity, 2024)

Non-native plant invasion after fire in western USA varies by functional type and with climate - Janet S. Prevéy; Catherine S. Jarnevich; Ian S. Pearse; Seth M. Munson; Jens T. Stevens; Kevin J. Barrett; Jonathan D. Coop; Michelle A. Day; David Firmage; Paula J. Fornwalt; Katharine M. Haynes; James D. Johnston; et al. (Biological Invasions, 2024)

Cryopreservation of Anopheles stephensi (MOSQUITO) EGGS: EFFECTS ON GENOTYPIC AND PHENOTYPIC CHARACTERISTICS - Morgan Douglas; Ehud Inbar; Igor Sharakov; Najib M. El-Sayed; Ashton T. Belew; James Overby; Steve Matheny; Fantahun Addisu; Yonas Abebe; Dimitri Koutzoumis; Kerri Springer; Abraham Eappen; et al. (Cryobiology, 2023)

Refuge‐yeah or refuge‐nah? Predicting locations of forest resistance and recruitment in a fiery world - Kyle C. Rodman; Kimberley T. Davis; Sean A. Parks; Teresa B. Chapman; Jonathan D. Coop; Jose M. Iniguez; John P. Roccaforte; Andrew J. Sánchez Meador; Judith D. Springer; Camille S. Stevens‐Rumann; Michael T. Stoddard; Amy E. M. Waltz; et al. (Global Change Biology, 2023)
Climate warming, land use change, and altered fire regimes are driving ecological transformations that can have critical effects on Earth's biota. Fire refugia—locations that are burned less frequently or severely than their surroundings—may act as sites of relative stability during this period of rapid change by being resistant to fire and supporting post‐fire recovery in adjacent areas. Because of their value to forest ecosystem persistence, there is an urgent need to anticipate where refugia are most likely to be found and where they align with environmental conditions that support post‐fire tree recruitment. Using biophysical predictors and patterns of burn severity from 1180 recent fire events, we mapped the locations of potential fire refugia across upland conifer forests in the southwestern United States (US) (99,428 km 2 of forest area), a region that is highly vulnerable to fire‐driven transformation. We found that low pre‐fire forest cover, flat slopes or topographic concavities, moderate weather conditions, spring‐season burning, and areas affected by low‐ to moderate‐severity fire within the previous 15 years were most commonly associated with refugia. Based on current (i.e., 2021) conditions, we predicted that 67.6% and 18.1% of conifer forests in our study area would contain refugia under moderate and extreme fire weather, respectively. However, potential refugia were 36.4% (moderate weather) and 31.2% (extreme weather) more common across forests that experienced recent fires, supporting the increased use of prescribed and resource objective fires during moderate weather conditions to promote fire‐resistant landscapes. When overlaid with models of tree recruitment, 23.2% (moderate weather) and 6.4% (extreme weather) of forests were classified as refugia with a high potential to support post‐fire recruitment in the surrounding landscape. These locations may be disproportionately valuable for ecosystem sustainability, providing habitat for fire‐sensitive species and maintaining forest persistence in an increasingly fire‐prone world.

Human perceptions of competing interests in springs ecosystem management on public land in southwestern United States - Andrew J. Lewis; Stefanie Kunze; Julie M. Mueller; Ryan A. Fitch; Abraham E. Springer (Groundwater for Sustainable Development, 2023)

A retrospective study on the clinical use and owner perception of venlafaxine efficacy as part of a multimodal treatment for canine fear, anxiety, and aggression - Natalie N. Maffeo; Cary M. Springer; Julia D. Albright (Journal of Veterinary Behavior, 2023)

Effects of transdermal mirtazapine and oral gabapentin as pre-veterinary visit pharmaceuticals for shelter cats - Vanessa Spano; Cary M. Springer; E’Lise Christensen; Julia D. Albright (Journal of Veterinary Behavior, 2023)

Cover and density of southwestern ponderosa pine understory plants in permanent chart quadrats (2002–2020) - Margaret M. Moore; Jeffrey S. Jenness; Daniel C. Laughlin; Robert T. Strahan; Jonathan D. Bakker; Helen E. Dowling; Judith D. Springer (Ecology, 2022)
This data set consists of 101 permanent 1 m × 1 m (1‐m 2 ) quadrats located within southwestern ponderosa pine ecosystems near Flagstaff, Arizona, USA. Individual plants in these quadrats were identified and mapped annually for 19 years (2002–2020). The original chart quadrats were established between 1912 and 1927 to determine the effects of domestic livestock grazing on herbaceous plants and pine seedlings. Today these data provide opportunities to examine the effects of climate and land‐use change on plant demography, population dynamics, and community processes. We provide the following data and data formats: (1) digitized maps of all plant locations in shapefile and geodatabase format, (2) shapefiles showing annual locations of each individual plant species, (3) annual maps of each quadrat in TIFF and PDF format, (4) annual basal area of each species per quadrat for species mapped as polygons, (5) tabular representation of polygon areas and centroid locations for plant species mapped as polygons, (6) tabular representation of point locations for plant species mapped as points, (7) plot‐scale 20 m × 20 m overstory tree canopy cover, tree basal area, parent material, and elevation, (8) quadrat‐scale information (e.g., quadrat site and number, coordinates in UTM Zone 12 and latitude/longitude, and descriptive comments for each quadrat), (9) plant species list, (10) summary of plant species observed in each quadrat, (11) summary of quadrats mapped by site and year, and (12) data formatted for use in Integral Projection Models (IPM) and plant population analyses. There are no copyright restrictions; please cite this paper and the associated data set when data are used in publications.

Correction to: Characterizing introgression‑by‑environment interactions using maize near isogenic lines - Zhi Li; Sara B. Tirado; Dnyaneshwar C. Kadam; Lisa Coffey; Nathan D. Miller; Edgar P. Spalding; Aaron J. Lorenz; Natalia de Leon; Shawn M. Kaeppler; Patrick S. Schnable; Nathan M. Springer; Candice N. Hirsch (Theoretical and Applied Genetics, 2021)

Quantifying the base flow of the Colorado River: its importance in sustaining perennial flow in northern Arizona and southern Utah (USA) - Riley K. Swanson; Abraham E. Springer; David K. Kreamer; Benjamin W. Tobin; Denielle M. Perry (Hydrogeology Journal, 2021)

The clinical and educational outcomes of an inter-professional student-led medication review team, a pilot study - Michael O. Reumerman; Milan C. Richir; Philippe M. Domela Nieuwenhuis; Rowan Sultan; Hester E. M. Daelmans; Hans Springer; Majon Muller; Michiel A. van Agtmael; Jelle Tichelaar (European Journal of Clinical Pharmacology, 2021)
Aims The involvement of an inter-professional healthcare student team in the review of medications used by geriatric patients could not only provide patients with optimized therapy but also provide students with a valuable inter-professional learning experience. We describe and evaluate the clinical and learning outcomes of an inter-professional student-run mediation review program (ISP). Subject and method A variable team consisting of students in medicine, pharmacy, master advanced nursing practice, and master physician assistant reviewed the medication lists of patients attending a specialized geriatric outpatient clinic. Results During 32 outpatient visits, 188 medications were reviewed. The students identified 14 medication-related problems, of which 4 were not recognized by healthcare professionals. The ISP team advised 95 medication changes, of which 68 (71.6%) were directly implemented. Students evaluated this pilot program positively and considered it educational (median score 4 out of 5) and thought it would contribute to their future inter-professional relationships. Conclusion An inter-professional team of healthcare students is an innovative healthcare improvement for (academic) hospitals to increase medication safety. Most formulated advices were directly incorporated in daily practice and could prevent future medication-related harm. The ISP also offers students a first opportunity to work in an inter-professional manner and get insight into the perspectives and qualities of their future colleagues.

Characterizing introgression-by-environment interactions using maize near isogenic lines - Zhi Li; Sara B. Tirado; Dnyaneshwar C. Kadam; Lisa Coffey; Nathan D. Miller; Edgar P. Spalding; Aaron J. Lorenz; Natalia de Leon; Shawn M. Kaeppler; Patrick S. Schnable; Nathan M. Springer; Candice N. Hirsch (Theoretical and Applied Genetics, 2020)

10th Anniversary of the European Association for Predictive, Preventive and Personalised (3P) Medicine - EPMA World Congress Supplement 2020 - Olga Golubnitschaja; Ondrej Topolcan; Radek Kucera; Vincenzo Costigliola; M. Akopyan; S. N. Akulov; O Alexandrova; Angel Alonso; Russell J. Andrews; A Assuane Duarte; O. Azarova; Maximilian Babel; et al. (EPMA Journal, 2020)
In 2019, the EPMA celebrated its 10th anniversary at the 5th World Congress in Pilsen, Czech Republic. The history of the International Professional Network dedicated to Predictive, Preventive and Personalised Medicine (PPPM / 3PM) is rich in achievements. Facing the coronavirus COVID-19 pandemic it is getting evident globally that the predictive approach, targeted prevention and personalisation of medical services is the optimal paradigm in healthcare demonstrating the high potential to save lives and to benefit the society as a whole. The EPMA World Congress Supplement 2020 highlights advances in 3P medicine.

Biogeography of shell morphology in over‐exploited shellfish reveals adaptive trade‐offs on human‐inhabited islands and incipient selectively driven lineage bifurcation - Ashley M. Hamilton; Jason D. Selwyn; Rebecca M. Hamner; Hokuala K. Johnson; Tia Brown; Shauna K. Springer; Christopher E. Bird (Journal of Biogeography, 2020)
Aim Humans are unintentionally affecting the evolution of fishery species directly through exploitation and indirectly by altering climate. We aim to test for a relationship between biogeographic patterns in the shell phenotypes of an over‐exploited shellfish and the presence of humans to identify human‐mediated adaptive trade‐offs. The implications of these trade‐offs are discussed with respect to the sustainability of the fishery. Taxon The endemic Hawaiian intertidal limpet, ‘opihi makaiauli (Patellagastropoda, Nacellidae, Cellana exarata) Methods We surveyed phenotypic characters associated with temperature and predation avoidance across the entire species range and tested for differences in the relationship between these characters and latitude, on islands with and without humans. Results Among all limpets surveyed, there was a bimodal distribution in shell colour (light, dark) and a parapatric pattern of shell coloration across the archipelago with lighter shells being prevalent on the uninhabited islands and darker, more camouflaged shells being prevalent on the inhabited islands. On the cooler, uninhabited islands, all morphometric characters associated with thermal avoidance (surface area, height and doming) increased with decreasing latitude. On the hotter, inhabited islands, however, shells were flatter, less variable and less adapted for avoiding thermal stress than predation. Main Conclusions The biogeographic patterns in shell phenotype and previous genetic studies suggest that the population is beginning to bifurcate in response to disruptive and directional selection as well as geographic isolation between the islands with and without humans. Decreased phenotypic and genetic diversity on the inhabited islands despite much larger populations of ‘opihi suggests a prominent historical bottleneck. The prevalence of maladaptive dark, flat phenotypes for thermal avoidance on the inhabited islands suggests that predation is a stronger selective force, driving adaptive trade‐offs in shape and colour. We propose that this is likely a case of fisheries‐induced evolution and a millennium of harvesting is the most likely selective pressure driving the observed biogeographic patterns in shell morphology. The flatter, darker shells will allow body temperatures to rise higher in direct sunlight, therefore we hypothesize that the thermal niche of ‘opihi is narrower on inhabited islands and will continue to narrow as Earth warms.

Correction to: Review of GPS collar deployments and performance on nonhuman primates - Kerry M. Dore; Malene F. Hansen; Amy R. Klegarth; Claudia Fichtel; Flávia Koch; Andrea Springer; Peter Kappeler; Joyce A. Parga; Tatyana Humle; Christelle Colin; Estelle Raballand; Zhi-Pang Huang; et al. (Primates, 2020)

Review of GPS collar deployments and performance on nonhuman primates - Kerry M. Dore; Malene F. Hansen; Amy R. Klegarth; Claudia Fichtel; Flávia Koch; Andrea Springer; Peter Kappeler; Joyce A. Parga; Tatyana Humle; Christelle Colin; Estelle Raballand; Zhi-Pang Huang; et al. (Primates, 2020)

Effect of removal of bacteria on the biomass and extracellular carbohydrate productivity of Botryococcus braunii - Joao D. Gouveia; Antoine Moers; Yvonne Griekspoor; Lambertus A. M. van den Broek; Jan Springer; Lolke Sijtsma; Detmer Sipkema; Rene H. Wijffels; Maria J. Barbosa (Journal of Applied Phycology, 2019)

Correction to: Lung cancer screening: an emerging cancer control issue presents opportunities for an awareness campaign in rural Michigan - Steven M. Springer; Angela McFall; Polly Hager; Antoinette Percy-Laurry; Cynthia A. Vinson (Cancer Causes & Control, 2019)

Demonstrating developments in high-fidelity analytical radiation force modelling methods for spacecraft with a new model for GPS IIR/IIR-M - S. Bhattarai; M. Ziebart; S. Allgeier; S. Grey; T. Springer; D. Harrison; Z. Li (Journal of Geodesy, 2019)

Springs ecosystems: vulnerable ecological islands where environmental conditions, life history traits, and human disturbance facilitate non-native plant invasions - Kayleigh G. Nielson; Karen M. Gill; Abraham E. Springer; Jeri D. Ledbetter; Lawrence E. Stevens; Stewart B. Rood (Biological Invasions, 2019)

Lung cancer screening: an emerging cancer control issue presents opportunities for an awareness campaign in rural Michigan - Steven M. Springer; Angela McFall; Polly Hager; Antoinette Percy-Laury; Cynthia A. Vinson (Cancer Causes & Control, 2018)

Socio-environmental consideration of phosphorus flows in the urban sanitation chain of contrasting cities - Geneviève S. Metson; Steve M. Powers; Rebecca L. Hale; Jesse S. Sayles; Gunilla Öberg; Graham K. MacDonald; Yusuke Kuwayama; Nathaniel P. Springer; Anthony J. Weatherley; Kelly L. Hondula; Kristal Jones; Rubel B. Chowdhury; et al. (Regional Environmental Change, 2018)

Favourable outcome in a child with symptomatic diagnosis of Glutaric aciduria type 1 despite vertical HIV infection and minor head trauma - Angeline Thomas; Els F. M. Dobbels; Priscilla E. Springer; Christelle Ackermann; Mark F. Cotton; Barbara Laughton (Metabolic Brain Disease, 2018)

Variability in C-reactive protein is associated with cognitive impairment in women living with and without HIV: a longitudinal study - Leah H. Rubin; Lorie Benning; Sheila M. Keating; Philip J. Norris; Jane Burke-Miller; Antonia Savarese; Krithika N. Kumanan; Saria Awadalla; Gayle Springer; Kathyrn Anastos; Mary Young; Joel Milam; et al. (Journal of NeuroVirology, 2018)

Erratum to: Low ambient oxygen prevents atherosclerosis - Ju-Gyeong Kang; Ho Joong Sung; Marcelo J. Amar; Milton Pryor; Alan T. Remaley; Michele D. Allen; Audrey C. Noguchi; Danielle A. Springer; Jaeyul Kwon; Jichun Chen; Ji-hoon Park; Ping-yuan Wang; et al. (Journal of Molecular Medicine, 2016)

Low ambient oxygen prevents atherosclerosis - Ju-Gyeong Kang; Ho Joong Sung; Marcelo J. Amar; Milton Pryor; Alan T. Remaley; Michele D. Allen; Audrey C. Noguchi; Danielle A. Springer; Jaeyul Kwon; Jichun Chen; Ji-hoon Park; Ping-yuan Wang; et al. (Journal of Molecular Medicine, 2016)

Utilization of deletion bins to anchor and order sequences along the wheat 7B chromosome - Tatiana Belova; Lars Grønvold; Ajay Kumar; Shahryar Kianian; Xinyao He; Morten Lillemo; Nathan M. Springer; Sigbjørn Lien; Odd-Arne Olsen; Simen R. Sandve (Theoretical and Applied Genetics, 2014)

Antagonism of brain insulin-like growth factor-1 receptors blocks estradiol effects on memory and levels of hippocampal synaptic proteins in ovariectomized rats - Britta S. Nelson; Rachel C. Springer; Jill M. Daniel (Psychopharmacology, 2014)

An institutional strategy to increase minority recruitment to therapeutic trials - Victoria V. Anwuri; Lannis E. Hall; Katherine Mathews; Brian C. Springer; Jennifer R. Tappenden; Dione M. Farria; Sherrill Jackson; Melody S. Goodman; Timothy J. Eberlein; Graham A. Colditz (Cancer Causes & Control, 2013)

Resource partitioning by sympatric pagophilic seals in Alaska: monitoring effects of climate variation with fatty acids - Margaret H. Cooper; Suzanne M. Budge; Alan M. Springer; Gay Sheffield (Polar Biology, 2009)

Trend data do support the sequential nature of pinniped and sea otter declines in the North Pacific Ocean, but does it really matter? - J. A. Estes; D. F. Doak; A. M. Springer; T. M. Williams; G. B. Van Vliet (Marine Mammal Science, 2009)

Nocturnal activity by mammal‐eating killer whales at a predation hot spot in the Bering Sea - K. Newman; A. M. Springer (Marine Mammal Science, 2008)

Tracing carbon flow in an arctic marine food web using fatty acid-stable isotope analysis - S. M. Budge; M. J. Wooller; A. M. Springer; S. J. Iverson; C. P. McRoy; G. J. Divoky (Oecologia, 2008)

Restoring plant species diversity and community composition in a ponderosa pine-bunchgrass ecosystem - Daniel C. Laughlin; Jonathan D. Bakker; Mark L. Daniels; Margaret M. Moore; Cheryl A. Casey; Judith D. Springer (Plant Ecology, 2008)

Mammal‐eating killer whales, industrial whaling, and the sequential megafaunal collapse in the North Pacific Ocean: A reply to critics of Springer et al . 2003 - A. M. Springer; J. A. Estes; G. B. Van Vliet; T. M. Williams; D. F. Doak; E. M. Danner; B. Pfister (Marine Mammal Science, 2008)

Fatty acid signatures of stomach oil and adipose tissue of northern fulmars (Fulmarus glacialis) in Alaska: implications for diet analysis of Procellariiform birds - Shiway W. Wang; Sara J. Iverson; Alan M. Springer; Scott A. Hatch (Journal of Comparative Physiology B, 2007)

Comprehensive trend analysis of nutrients and related variables in a large eutrophic estuary: A decadal study of anthropogenic and climatic influences - JoAnn M. Burkholder; David A. Dickey; Carol A. Kinder; Robert E. Reed; Michael A. Mallin; Matthew R. McIver; Lawrence B. Cahoon; Greg Melia; Cavell Brownie; Joy Smith; Nora Deamer; Jeffrey Springer; et al. (Limnology and Oceanography, 2006)
We used a decadal data set, with weekly to biweekly sampling in April—October and monthly sampling in November—March, to characterize climatic (hurricane‐level storms, a sustained 3‐yr drought) and anthropogenic influences on N and P concentrations and loadings to a large eutrophic, poorly flushed estuary, the Neuse Estuary of the Albemarle—Pamlico Estuarine System. Mass volume transport data were obtained with cross‐estuary transect flow measurements taken near the entrance to the estuary. Although trends were minimally influenced by hurricanes, analyses were significantly affected by the sustained drought near the end of the study. As examples, decreasing trends in total N (TN), total P (TP), and bottom‐water dissolved oxygen concentrations, and in TN loadings were significant considering all data, but these trends were not significant when the sustained drought was excluded from analysis. In addition, the trend in TN loading was especially sensitive to the initial sampling period. NH 4 + concentrations dramatically increased (overall by ~500%) as a persistent trend regardless of attempts to control for climatic events. An increasing trend in NH 4 + also was documented in an adjacent, rapidly flushed Coastal Plain estuary, the Cape Fear. The NH 4 + data suggest a regional‐scale effect of high inputs from inadequately controlled, increasing nonpoint sources. The fragility of TN loading trends, the striking increase in NH 4 + concentrations, and the lack of management emphasis on controlling nonpoint sources such as “new” industrialized swine production collectively do not support recent reports of achievement of a 30% reduction in TN loading to the Neuse. Nonpoint sources remain a critical target for reduction to alleviate the negative effects of cultural eutrophication in this system, as in many estuaries throughout the world.

Case Study Part 2: Probabilistic Modelling of Long-term Effects of Pesticides on Individual Breeding Success in Birds and Mammals - W. ROELOFS; D.R. CROCKER; R.F. SHORE; D.R.J. MOORE; G.C. SMITH; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; et al. (Ecotoxicology, 2005)

Case Study Part 1: How to Calculate Appropriate Deterministic Long-Term Toxicity to Exposure Ratios (TERs) for Birds and Mammals - R.F. SHORE; D.R. CROCKER; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; A. FAIRBROTHER; S. FERSON; D. FISCHER; et al. (Ecotoxicology, 2005)

Walking is more like catching than tapping: gait in the elderly as a complex cognitive task - Jeffrey M Hausdorff; Galit Yogev; Shmuel Springer; Ely S. Simon; Nir Giladi (Experimental Brain Research, 2005)

Structure–activity relationships in platinum–acridinylthiourea conjugates: effect of the thiourea nonleaving group on drug stability, nucleobase affinity, and in vitro cytotoxicity - Margaret C. Ackley; Colin G. Barry; Amanda M. Mounce; Michael C. Farmer; Beth-Erin Springer; Cynthia S. Day; Marcus W. Wright; Susan J. Berners-Price; Suzanne M. Hess; Ulrich Bierbach (JBIC Journal of Biological Inorganic Chemistry, 2004)

Molecular Evidence for the Last Survivor of an Ancient Kangaroo Lineage - Michael Westerman; Angela Burk; Heather M. Amrine-Madsen; Gavin J. Prideaux; Judd A. Case; Mark S. Springer (Journal of Mammalian Evolution, 2002)

Molecular Relationships of the New Guinean Bandicoot Genera Microperoryctes and Echymipera (Marsupialia: Peramelina) - M. Westerman; M. S. Springer; C. Krajewski (Journal of Mammalian Evolution, 2001)

Analysis of the first year of Earth rotation parameters with a sub-daily resolution gained at the CODE processing center of the IGS - J. Hefty; M. Rothacher; T. Springer; R. Weber; G. Beutler (Journal of Geodesy, 2000)

Maximum-Likelihood Analysis of the Tethythere Hypothesis Based on a Multigene Data Set and a Comparison of Different Models of Sequence Evolution - Heather M. Amrine; Mark S. Springer (Journal of Mammalian Evolution, 1999)

Improving the orbit estimates of GPS satellites - T. A. Springer; G. Beutler; M. Rothacher (Journal of Geodesy, 1999)

A New Solar Radiation Pressure Model for GPS Satellites - T. A. Springer; G. Beutler; M. Rothacher (GPS Solutions, 1999)

Cervical lymphadenitis due to an unusual mycobacterium - E. Tortoli; P. Kirschner; B. Springer; A. Bartoloni; C. Burrini; A. Mantella; M. Scagnelli; C. Scarparo; M. T. Simonetti; E. C. Böttger (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Impact of salt adaptation on esterified fatty acids and cytochrome oxidase in plasma and thylakoid membranes from the cyanobacterium Anacystis nidulans - V. Molitor; M. Trnka; W. Erber; I. Steffan; M. -E. Rivire; B. Arrio; H. Springer-Lederer; G. A. Peschek (Archives of Microbiology, 1990)

Determination of the DDE and PCB contents of peregrine Falcon eggs: A comparison of whole egg measurements and estimates derived from eggshell membranes - David B. Peakal'; Thomas S. Lew; Alan M. Springer; Wayman Walker IP; Robert W. Risebrough; J. Geoffrey Monk; Walter M. Jarman; Brian J. Walton; Lincoln M. Reynolds; Richard W. Fyfe; Lloyd F. Kiff (Archives of Environmental Contamination and Toxicology, 1983)